Exploring RECQ Helicase landscape in breast cancer - Arora, Arvind (2019)
Background Breast cancer is the second most common cause of cancer death in females in the UK. Approximately 20 percent of breast cancers diagnosed are triple negative (TNBC) intrinsic subtype, which are aggressive high-grade tumours carrying a poor prognosis. About 20% of TNBC harbour a mutation in breast cancer gene (BRCA). BRCA plays important role in homologous recombination. There is evidence to suggest that non-familial breast cancers harbour homologous recombination repair defects that may be useful targets for therapy.